The Growing Need to Understand Very Early Onset Inflammatory Bowel Disease - Zheng, Hengqi B.; de la Morena, M. Teresa; Suskind, David L. (Frontiers in Immunology, 2021)
Very Early Onset Inflammatory Bowel Disease (VEO-IBD) represents a cohort of inflammatory bowel disease (IBD) patients diagnosed before 6 years of age. Unlike IBD diagnosed at older ages, VEO-IBD can be associated with underlying primary immunodeficiencies. VEO-IBD has been linked to monogenic variations in over 70 genes involved in multiple pathways of immunity. As sequencing technologies and platforms evolve and become readily available, an increasing number of genes linked to VEO-IBD have emerged. Although monogenic defects are rare in VEO-IBD, diagnosis of these variants can often dictate specific treatment. In this mini-review, we set out to describe monogenic variants previously characterized in multiple patients in the literature that contribute to VEO-IBD, diagnostic tools, unique treatment modalities for specific genetic diagnoses, and future directions in the field of VEO-IBD. Although this mini-review is by no means comprehensive of all the novel monogenic variants linked to VEO-IBD, we hope to provide relevant information that is readily accessible to clinicians and educators.